2022
DOI: 10.3390/ijerph19095719
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Age, Sex, and Viral Load in Outpatients during the Four Waves of SARS-CoV-2 in A Mexican Medium-Sized City

Abstract: Governments have implemented measures to minimize SARS-CoV-2 spread. However, these measures were relaxed, and the appearance of new variants has prompted periods of high contagion known as waves. In Mexico, four waves distributed between July and August 2020, January and February 2021, August and September 2021, and January and February 2022 have appeared. Current health policies discourage mass sampling, preferring to focus on the corrective treatment of severe cases. Outpatients are only advised to undergo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 51 publications
1
6
0
1
Order By: Relevance
“…The maximum viral loads for Delta VOC were approximately 125,000, 110,000, and 182,000 gene copies/100 mL for Saskatoon, Prince Albert, and North Battleford, respectively, while the greatest viral loads for Omicron were 201,000, 340,000, and 190,000 gene copies/100 mL, for Saskatoon, Prince Albert, and North Battleford, respectively. Another study has shown that the viral load associated with Omicron was very high compared to the earlier viral loads from Alpha, Delta, and Beta ( Covantes-Rosales et al, 2022 ). This large load of virus particles observed for Omicron could directly relate to its increased rate of infection because of its ability to infect vaccinated people.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The maximum viral loads for Delta VOC were approximately 125,000, 110,000, and 182,000 gene copies/100 mL for Saskatoon, Prince Albert, and North Battleford, respectively, while the greatest viral loads for Omicron were 201,000, 340,000, and 190,000 gene copies/100 mL, for Saskatoon, Prince Albert, and North Battleford, respectively. Another study has shown that the viral load associated with Omicron was very high compared to the earlier viral loads from Alpha, Delta, and Beta ( Covantes-Rosales et al, 2022 ). This large load of virus particles observed for Omicron could directly relate to its increased rate of infection because of its ability to infect vaccinated people.…”
Section: Resultsmentioning
confidence: 94%
“…This is particularly true because access to clinical testing and analytical facilities are prioritized for certain populations at greater risk for severe outcomes due to infection with COVID-19 ( SHA, 2022 ; Arts et al, 2022 ). Hence, accessibility to clinical testing is limited to certain segments of the population ( Covantes-Rosales et al, 2022 ). Therefore, to accurately identify and quantify prevalence of SARS-CoV-2 in a population, including variants of concern, wastewater surveillance appears to be the most promising public health alternative to individual mass testing.…”
Section: Introductionmentioning
confidence: 99%
“…30 Delta and Omicron variants have shorter incubation periods, whereas higher infectious viral loads were detected in patients infected with Delta than in patients infected with Omicron. 31,32 The clearance time of viral load is slower in non-vaccinated individuals. 33 After one dose of vaccine, the number of Ct increased by 4.5 Ct, and with a booster, it increased by 2.4 Ct 34 ; therefore, the start of vaccination could be a factor that influenced our results; nevertheless, the combined treatment reached the effect faster in Ct, and a larger effect size in reducing viral load at seven days; some antivirals found a significant reduction in viral load, 22,23 remdesivir no provoke reduction, only positive clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…COVID‐19 is caused by SARS‐CoV‐2 virus first identified in Wuhan, China around December 2019 and spread globally 1,2 . The virus spread through internationally and reached Mexico February 28, 2020 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…COVID‐19 is caused by SARS‐CoV‐2 virus first identified in Wuhan, China around December 2019 and spread globally. 1 , 2 The virus spread through internationally and reached Mexico February 28, 2020. 2 , 3 Since then, over 7 million confirmed cases of COVID‐19 and over 300,000 have occurred in Mexico.…”
Section: Introductionmentioning
confidence: 99%